A rare case: Asymptomatic spontaneous pneumobilia - Yeniocak, Selman; Az, Adem; Canıpek, Eda; Ekinci Biçkici, Büşra; Metiner, Merve; Demirel, Ahmet (Journal of Surgery and Medicine, 2019)
Pneumobilia, or aerobilia, is defined as the presence of gas in the biliary system. It may occur for various reasons, including recent enterobiliary system interventions, sphincter of oddi dysfunction, and enterobiliary fistula and anastomoses. A 61-year-old male patient presented to our emergency department due to nausea and vomiting. He had no history of drug use other than proton pump inhibitor medication, nor of alcohol or substance use. Although no history of previous medical intervention was present, gas (pneumobilia) was detected in the intrahepatic biliary ducts. We suspected that the incidentally detected pneumobilia in this patient, who also suffered from food poisoning, developed spontaneously in association with peptic ulcer and might have derived from a thin, asymptomatic enterobiliary fistula. Depending on its cause, pneumobilia may not require emergency surgery. The possibility of enterobiliary fistula should not be overlooked in patients presenting to the emergency department with chronic peptic ulcer symptoms.